Peace Strategies and Approaches for Resolving the Conflict of Terrorism in Indonesia - Misran, Misran (Jurnal Keamanan Nasional, 2022)
The end of the Cold War marked the shift of world threats from traditional military threats to asymmetric non-traditional threats of terrorism. Terrorist groups emerge with various backgrounds. Domestic political instability in the form of conflict and separatism to revenge motivation or being affected by the threat of terrorism in other countries. The purpose of this research is to analyze the strategy and approach of peace to resolve the terrorism conflict. The method used in this research is the literature review. The data sources in this study were taken from the Scopus database and several other databases such as Connected Papers, Open knowledge maps, and Google Scholar to support this research, then some data were taken from the news. The findings in this study emphasize that apart from the hard approach and also the soft approach as an approach to resolving the conflict of terrorism, there are other approaches that can be used as an alternative approach, namely the conflict triangle where this approach has not been widely adopted in Indonesia.